Asymmetric inheritance of mTORC1 kinase activity during division dictates CD8+ T cell differentiation - Pollizzi, Kristen N; Sun, Im-Hong; Patel, Chirag H; Lo, Ying-Chun; Oh, Min-Hee; Waickman, Adam T; Tam, Ada J; Blosser, Richard L; Wen, Jiayu; Delgoffe, Greg M; Powell, Jonathan D (Nature immunology, 2016)
Asymmetric division can generate effector and memory CD8 + T cell precursors. Powell and colleagues show asymmetric partitioning of mTORC1 activity upon CD8 + T cell division, which results in distinct metabolic programming of daughter T cells. The asymmetric partitioning of fate-determining proteins has been shown to contribute to the generation of CD8 + effector and memory T cell precursors. Here we demonstrate the asymmetric partitioning of mTORC1 activity after the activation of naive CD8 + T cells. This results in the generation of two daughter T cells, one of which shows increased mTORC1 activity, increased glycolytic activity and increased expression of effector molecules. The other daughter T cell has relatively low mTORC1 activity and increased lipid metabolism, expresses increased amounts of anti-apoptotic molecules and subsequently displays enhanced long-term survival. Mechanistically, we demonstrate a link between T cell antigen receptor (TCR)-induced asymmetric expression of amino acid transporters and RagC-mediated translocation of mTOR to the lysosomes. Overall, our data provide important insight into how mTORC1-mediated metabolic reprogramming affects the fate decisions of T cells.